Разработка пирамидального метода сегментации изображения - Пархоменко, В. А. (My University, 2011)
The primary problem of the segmentation pyramidic stages is an association nearby element in one segment on criterion of homogeneity. Method is realized by image partition on n+ 1 layer before reduction of the image sizes using change threshold factor.
Keywords: сегментация изображений; сегментация